Drastic changes in a lower-trophic-level ecosystem attributed to unprecedented harmful algal outbreaks in 2021 on the Pacific shelf off southeast Hokkaido, Japan - Taniuchi, Yukiko; Watanabe, Tsuyoshi; Azumaya, Tomonori; Takagi, Satomi; Kasai, Hiromi; Nakanowatari, Takuya; Ohnishi, Takuya; Kakehi, Shigeho; Kuroda, Hiroshi (Continental shelf research, 2023)
Unprecedented, large-scale harmful algal blooms (HABs) occurred in Pacific coastal shelf waters off the southeastern coast of Hokkaido, Japan, in the autumn of 2021. To understand how these HABs, composed primarily of Karenia selliformis, changed the structures of lower-trophic-level ecosystems in shelf waters, we analyzed high-resolution in situ ship measurements taken during October 2015–2021. We mainly compared physico-biochemical variables averaged over the shelf in 2021 and in 2015–2020. Chlorophyll-a concentrations at a depth of 10 m were approximately 2.3-fold higher in 2021 than in 2015–2020. Chlorophyll-a concentrations were highest at the sea surface in 2021, and vertically integrated concentrations were 1.8-fold higher in 2021 than in 2015–2020. Silicate concentrations at a depth of 10 m were higher in 2021, whereas nitrate and phosphate concentrations were largely the same. Abundances of major diatoms and picophytoplankton (e.g., Synechococcus spp.) at a depth of 10 m declined by 2 orders and 1 order of magnitude in 2021, respectively, whereas Karenia spp. abundance greatly increased. These results indicated that outbreaks of K. selliformis suppressed the growth of other algal species and dramatically changed nutrient flows and balances in the coastal shelf ecosystem. The suppression of non-Karenia algal species might have occurred through interspecific competition for nutrients as well as allelopathy and/or mixotrophy by K. selliformis. •Environmental variables at 10-m depth were compared between 2015–2020 and 2021.•The lower-trophic-level ecosystem was changed greatly by Karenia outbreaks in 2021.•Chlorophyll-a and silicate concentrations were higher in 2021.•Nitrate and phosphate concentrations were relatively unchanged in 2021.•Major diatoms and picophytoplankton were less abundant in 2021.